PENGARUH PERLAKUAN PERENDAMAN BIJI KAKAO TERHADAP KARAKTERISTIK COKELAT BATANG - , ANNISA LATHIFANI, Prof. Dr. Ir. E. Purnama Darmadji, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The cacao plantations of commodities is important for the economy in Indonesia. Cacao can be processed into a product with a higher sale price. Processed cacao products which are of fine quality are strongly influenced by the quality of the cacao beans are used. When cacao beans are used very low and the results obtained will be low. One of the weakness of the quality of cacao beans originating in indonesia was a level of acidity is high. Because of that required a method to reduce contens of the high acid on cacao beans.The aim of this research is to reduce contens of the acid that is too high on driedcacao beans, so that when the roasted stage on dried cocoa beans can produce flavor that is more potent and to identify a compound flavor in chocolate the stems which are derived from cocoa beans fermented and non fermented. The mechanism of this research is to perform the process of the manufacture of chocolate bar with wide variations time soaking and without soaking as well as a kind of cocoa beans are used. Dried cacao beans fermented and non fermented given early treatment is soaking with some variation time, namely 30 60, 90 and 120 minutes before stage of the roasting process.Next phase is chemical analysis and organoleptic. The result showed that the treatment of soaking dried cacao beans fermented and non fermented before roated stages can improve the quality of chocolate bar with a sour taste, lowering theobromin levels, and activate a compound precursor of a flavor before roasted stages. Volatile components dominant detected in brown chocolate bar from cacao beans non fermented and fermentedwith soaking treatment and chocolate bar from cacao beans fermented without soaking treatment is nonanal with an aroma description green and woody. While in chocolate bar from cacao beans non fermented without soaking treatment components dominant is phenylethyl alcohol with an aroma description chocolate and acid. Keyword : Cacao beans, chocolate bar, soaking, volatile components